Contemporary selection on MHC genes in a free‐living ruminant population. (20th January 2022) - Huang, Wei; Dicks, Kara L.; Hadfield, Jarrod D.; Johnston, Susan E.; Ballingall, Keith T.; Pemberton, Josephine M.
Abstract: Genes within the major histocompatibility complex (MHC) are the most variable identified in vertebrates. Pathogen‐mediated selection is believed to be the main force maintaining MHC diversity. However, relatively few studies have demonstrated contemporary selection on MHC genes. Here, we examine associations between MHC variation and several fitness measurements including total fitness and five fitness components, in 3400 wild Soay sheep (Ovis aries ) monitored between 1989 and 2012. In terms of total fitness, measured as lifetime breeding success of all individuals born, we found haplotypes named C and D were associated with decreased and increased male total fitness respectively. In terms of fitness components, juvenile survival was associated with haplotype divergence while individual haplotypes (C, D and F) were associated with adult fitness components. Consistent with the increased male total fitness, the rarest haplotype D has increased in frequency throughout the study period more than expected under neutral expectations. Our results demonstrate that contemporary natural selection is acting on MHC class II genes in Soay sheep and that the mode of selection on specific fitness components can be different mode from selection on total fitness. Abstract : The major histocompatibility complex (MHC) is one of the most variable gene families in vertebrates. Parasite‐mediated selection is believed to be the main force maintaining diversity at MHC genes, but demonstrating contemporary selection on MHC alleles in natural populations is not trivial. Here, we use haplotypes of expressed MHC class II genes in a large sample of individually monitored wild sheep to examine associations between MHC and fitness measurements and investigate change in MHC haplotype frequency over two decades. With this large data set, we demonstrate contemporary selection on MHC genes and highlight highlights the importance of investigating frequency change of MHC haplotype.